Odpowiedzi

2009-11-20T21:03:42+01:00
A) (3 7/8 + 4 5/8) - ( 9 1/8 - 5 5/8)=
8 4/8 - 3 4/8 = 5
b) (4 4/15 - 2 7/15) + (6 2/15 - 3 8/15)=
1 12/15 + 2 9/15=
3 21/15= 4 6/15= 4 2/5
d) 45 - 18 - (21 5/22 - 19 11/22) + (1 3/22 + 2 7/22)=
45- 18 - 1 6/22 + 3 10/22=
27 - 4 16/22= 22 6/22= 22 3/11
1 2 1
2009-11-20T21:04:02+01:00
A)(3 7/8+4 5/8)-(9 1/8-5 5/8)= 7 12/8-(73/8-45/8)=68/8-28/8=40/8=5
b)(4 4/15-2 7/15)+6 2/15-3 8/15)=
( 64/15 -37/15) +(92/15-53/15)=
27/15+39/15=66/15= 4 6/15
c )(8 3/20+ 6 18/20)-5 7/20-2 11/20)+4 1/20+1 9/20)=
14 21/20 -( 107/20 -51/20)+ 5 10/20=
15 1/20 - 2 16/20+5 10/20= 20 11/20-2 16/20= 17 15/20
d)45-18-(21 5/22-19 11/22)+ (1 3/22+2 7/22)=
27-1 16/22+ 3 10/22= 27 +1 18/22=28 18/22
1 3 1
Najlepsza Odpowiedź!
2009-11-20T22:52:02+01:00
A)(3 7/8+4 5/8)-(9 1/8-5 5/8)=7 12/18 - 3 4/8=4 8/8=5
b)(4 4/15-2 7/15)+6 2/15-3 8/15)=1 12/15 + 2 9/15= 3 21/15=4 6/15 =4 3/5
c )(8 3/20+ 6 18/20)-5 7/20-2 11/20)+4 1/20+1 9/20)=14 21/20-2 16/20+5 10/20=12 5/20+5 10/20= 17 15/20=17 3/4
d)45-18-(21 5/22-19 11/22)+ (1 3/22+2 7/22)=45-18-1 16/22 + 2 10/2= 27- 1 16/22 + 2 10/22= 25 6/22 + 2 10/22=27 16/22=27 8 /11
1 3 1